Terrorism and Cyberspace: A Phenomenon of Cyber-Terrorism as Transnational Crimes - Nadiah Khaeriah Kadir; Judhariksawan Judhariksawan; Maskun Maskun (Universitas Lampung, 2019)
The advancement of information technology is changing the pattern of radical group propaganda from conventional methods to the ways they use today, namely using the media and cyberspace, or what is also called as cyber-terrorism. The purpose of this study is to discuss the emergence of the currently experienced cyber-terrorism phenomenon. It is normative research through a literature study method by approaching statutes. The results of this study indicate that cyber-terrorism is a part of cybercrime that is qualified as transnational crime which refers to Article 3 of the United Nations Convention against Transnational Organized Crime. Currently, there are several laws/regulations regarding terrorism at the national, regional and international levels. However, these rules do not specifically regulate new developments in acts of terrorism through cyberspace or what is known as cyber-terrorism.